1970
DOI: 10.1126/science.169.3941.188
|View full text |Cite
|
Sign up to set email alerts
|

Differential Reactivity of Human Serums with Early Antigens Induced by Epstein-Barr Virus

Abstract: Inoculation of 64-10 or Raji cultures with Epstein-Barr virus derived from the HRI-K clone of the P3J Burkitt's lymphoma line caused abortive infections in most of the lymphoblastoid cells with synthesis of "early antigens" but few, if any, capsids. Antibodies to early antigens were detected by indirect immunofluorescence in serums of many patients with infectious mononucleosis, Burkitt's lymphoma, or nasopharyngeal carcinoma. These antibodies were rarely present in other serums even though some of them showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
205
1
2

Year Published

1975
1975
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 576 publications
(210 citation statements)
references
References 13 publications
2
205
1
2
Order By: Relevance
“…One important feature of NPC is that it is associated with Epstein-Barr virus (EBV) infection. The majority of NPC patients have a variety of EBV antigens, and anti-EBV antibody serological testing has become an important tool for NPC diagnosis (Henle et al, 1970;Henle et al, 1973;Ho et al, 1976;Lynn et al, 1985;Brooks et al, 1992;Cochet et al, 1993;Ng et al, 2006;Ai et al, 2012). Traditional assays of anti-EBV antibodies have been very useful in clinical diagnosis of NPC, however, high false-positive rates may occur in endemic areas (Chang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One important feature of NPC is that it is associated with Epstein-Barr virus (EBV) infection. The majority of NPC patients have a variety of EBV antigens, and anti-EBV antibody serological testing has become an important tool for NPC diagnosis (Henle et al, 1970;Henle et al, 1973;Ho et al, 1976;Lynn et al, 1985;Brooks et al, 1992;Cochet et al, 1993;Ng et al, 2006;Ai et al, 2012). Traditional assays of anti-EBV antibodies have been very useful in clinical diagnosis of NPC, however, high false-positive rates may occur in endemic areas (Chang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Serum IgA concentration was found to be significantly higher in NPC patients than in control subjects (Wara et al, 1975;Ho et al, 1976). Henle and Henle (1976) reported that NPC patients have high titres of IgA antibody against viral capsid antigen (VCA) (Henle and Henle, 1966) and early antigens (EA) (Henle et al, 1970). These reactivities are detected less frequently and occur at lower titres in sera from patients with Burkitt's lymphoma (BL) and infectious mononucleosis (IM).…”
mentioning
confidence: 99%
“…Ten ul of a standard pod1 of EBV positive sera (EBV nuclear antigen, EBNA 1 : 400, EBV early antigen, EA I : 1200, VCA 1 : 6600, the titers were determined using standard immunofluorescent techniques, EBNA (Reedman and Klein, 1973), EA (Henle et al, 1970), VCA (Henle and Henle, 1966)) were mixed with 1OO~lofanextract prepared from EBV-negative BJA cells ( lo8 cells/ml buffer) and if required an aliquot equivalent to lo7 antigen-positive cells. The mixture was then incubated overnight at 4°C.…”
Section: Adsorption Of Human Seramentioning
confidence: 99%